Workplace bullying in the New Zealand nursing profession: the case for a tailored approach to intervention : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Human Resource Management at Massey University, Albany, New Zealand - Blackwood, Kate Marie (Massey University, 2015)
This thesis explores intervention in the workplace bullying experiences of New Zealand hospital nurses. Workplace bullying is a recognised problem internationally, and nursing is a high risk profession for such ill-treatment. With existing studies mapping the workplace bullying terrain, the research field is now moving towards how best to manage the problem. Recent research has identified numerous barriers to effective intervention and, as a result, existing studies recognise the need for a different approach that considers the impact of the work environment on intervention efficacy. The aim of this study is to understand how the work environment influences intervention in workplace bullying. Specifically, the research was guided by two questions: i) how do targets of workplace bullying in the New Zealand nursing profession represent their intervention experiences? and ii) how do work environment factors impact on the intervention experiences of targets of workplace bullying in the New Zealand nursing profession? The findings of this research are informed by 34 semi-structured interviews with targets of workplace bullying and three focus groups with organisational representatives responsible for bullying intervention. Thematic analysis of the interviews resulted in the development of an holistic intervention process model portraying how targets represent their intervention experiences. Subsequent thematic analysis of the interview and focus group data identified how a number of contextual and work environment factors influence the intervention process model. The model explains three key stages of intervention, namely identification of a bullying experience, reporting and intervention agent response, and how each of these stages influences the final outcome of an intervention experience for targets of workplace bullying. Specifically, the cyclical and iterative way in which these stages are experienced by targets is emphasised. A number of contextual and work environment factors that are barriers or facilitators in the intervention experience are explained. To explain the influence of contextual factors, five types of bullying experience are presented, each with a unique set of features that influence intervention in different ways, emphasising the heterogeneous nature of workplace bullying. Work environment factors are also identified as influencing the intervention process, providing empirical support for an extension of the work environment hypothesis to intervention in workplace bullying experiences. Tailored intervention strategies are recommended in light of the findings.
Listed in 2015 Dean's List of Exceptional Theses
Keywords: Workplace bullying; Nursing, New Zealand; Bullying intervention; Workplace environment; Dean's List of Exceptional Theses